The role of gabapentin in reducing postoperative pain and opioid consumption - Jamal Sulimani, Rami; Alharbi, Meshal Saud; Sulayman, Mohammad Laith; Khars, Hussain Sameer Al; Alhusainan, Abdullah Omar; Alzahrani, Sultan Mohammed; Alharthi, Waleed Jarallah; Saleh, Yousif Abdullatif Al; Alzahrani, Adel Saud; Alshehri, Abdullatif Saleh (International Journal Of Community Medicine And Public Health, 2024)
Effective postoperative pain management is essential for improving patient comfort, preventing complications like chronic pain, and reducing recovery times and hospital stays. Gabapentin, originally developed as an anticonvulsant, has gained attention for its potential role in managing postoperative pain and reducing opioid consumption. This literature review explores the effectiveness of gabapentin in various surgical contexts, focusing on its mechanism of action, safety profile, and impact on postoperative pain and opioid usage. Key findings from detailed trials indicate that gabapentin can effectively reduce pain scores and opioid consumption, particularly within the first 24 hours post-surgery. Studies in breast cancer surgery, spinal surgery, laparoscopic cholecystectomy, and arthroscopic procedures highlight its varying degrees of efficacy. While gabapentin consistently demonstrates opioid-sparing benefits and a favorable safety profile, its impact on pain reduction can differ based on the type of surgery. The review underscores the importance of tailoring gabapentin use to specific surgical and patient contexts for optimal outcomes. Continued research is recommended to refine dosage strategies and expand its application in multimodal pain management protocols.